Perbedaan Penyulit pada Masa Perinatal Ibu dengan Riwayat Diabetes Mellitus Gestasional dan Obesitas di RSUD Kabupaten Kediri - Ratna Hidayati; Devin Setyorini; Nian Afrian Nuari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
Complications in the perinatal period are abnormal. Factors of complications can be seen from the time of pregnancy, labor and post-partum. The aim of this research is to know the difference of complication at the time of perinatal mother with history of Diabetes Mellitus Gestional and Obesity. Design of this research was comparative with a restrospective approach. This research was conducted in March-April 2018 in the medical record room of Kediri Regency Hospital. Case samples were taken by purposive sampling technique of 50 respondents of pregnant women with a history of Diabetes Mellitus Gestational and with obesity history. Independent variables with a history of Gestational Diabetes Mellitus and Obesity and dependent variables were perinatal complications and maternal. Using Chi Square statistical test data is analyzed by calculating odds ratio. The result showed that the odds ratio was shown by estimate value of 0.365 and p value = 0,015 (<0,05). H1 received OR<1 this means pregnant women with Gestational Diabetes Mellitus have a risk factor 0,3 times the risk of experiencing complications than pregnant women with a history of Obesity. Therefore the role of nurses need to provide socialization to lower blood sugar levels and perform routine ANC so that thus reducing the risk of complications.